Non-specific vaccination exerts anti-tumor effect through CD11c (+) cells stimulation in a breast cancer model - de Gregorio, Vanessa Elizabeth (2016)
Background: Immunotherapy by using non-specific vaccines has proven to be effective in experimental animal models and also in patients suffering cancer. In the present work, the effectiveness of this immunotherapy was evaluated using a murine breast cancer model and a polymicrobial vaccine. Methodology/Principal: Mice bearing injected with tumor cells from the spontaneous syngeneic mammary adeno carcinoma M3 were used as breast cancer model. The immune adjuvant effect of the vaccine was analyzed in comparison or in the presence of doxorubicin. Tumor volume was calculated. Tumor, spleen and lymph nodes were processed for histological observations and to determinate the percentage of CD11c (+) cells. Results: Mice treated with the vaccine or with doxorubicin decreased tumor growth, with less tumor cell invasion. Tumor tissues showed decreased necrosis and nuclear areas in mice that received any of the treatments under study, compared with the control group. The benefits of vaccination were associated to stimulation of the immune response. More hyperplasia of the red and white pulp, and increased marginal megakaryocytes were observed in the spleens from mice treated with the vaccine. CD11c (+) cells did not increase  in tumor draining nodes by the immune stimulating effect of the vaccine; however,  his treatment increased CD11c (+) cells in the spleen and tumor. Conclusions: A non-specific vaccine used as immunotherapy can be used to prolong an equilibrium phase in  he tumor growth, similar to the doxorubicin treatment used in the model, although by different mechanisms. Non synergic effect was observed in the group treated with both vaccine and doxorubicin (low dose). Future studies should be necessary to evaluate the correct combination of vaccination and cytotoxic drug can be used for this purpose and to achieve increased activated dendritic cells in the tumor draining lymph nodes.